The Effect of Recycling Vocabulary on Foreign Language Learning - HAMDANE, Mohamed; HAMDANE, Ali (International Journal of Linguistics and Translation Studies, 2024)
The recycling method is frequently given a tiny proportion, if not neglected, in the practice of foreign language settings, although the multiple exposure strategy to language was given substantial priority in the theory and study of second language acquisition. This experimental study used a pre-and-post-testing design and a post-teaching intervention to examine the impact of vocabulary recycling on the learning of English as a foreign language. To assess the impact of the vocabulary recycling strategy, the researchers compared the experimental group of 33 high school student's vocabulary production on writing assessments before and after the intervention to the control group of 33 students with equal levels of homogeneity. The statistical differences in the post-test between the groups demonstrated that a vocabulary-revisiting strategy is compulsory for enhancing young learners' productive abilities, particularly writing. The derived conclusions suggest significant implications for pedagogical practices and pave the way for future research in this arena.